Contextualizing Geometry Learning for Elementary Students Through Ethnomathematics-Based Electronic Novels: A Developmental Research - Zaid Zainal; Halija Halija; Wawan Krismanto (Universitas Pendidikan Mandalika, 2026)
Mathematics learning outcomes in elementary schools remain suboptimal, partly due to the lack of contextualized learning. There are not many alternative learning media options available for teachers to facilitate contextual mathematics learning. Therefore, this study aims to design and develop an e-novel for elementary school geometry. This research is a research and development, with the 4D development model. This research was conducted at SDN 038 Kanusuang, SDN 034 Rappang, and SDN 019 Sila-Sila, Poliwali Mandar Regency, West Sulawesi, Indonesia. The research subjects included two validators (media experts and material experts), three class teachers, and all fifth-grade students from three schools. After going through the 4D stage, an e-novel development product was produced. The characteristics of e-novel product possesses are a story-based digital media, containing narratives, dialogues, illustrations, and learning activities that connect mathematical concepts with the local Mandar cultural context. Based on the results of the validity test conducted by media experts and material experts, as well as the practicality test conducted by teachers and students, the product was deemed highly valid (average score 90%) and categorized as very practical (average score 95,47%). Thus, the developed ethnomathematics-based e-novel are valid dan practical for use as a learning medium for geometry in fifth-grade elementary schools. Although there are still weaknesses, it has not yet reached the stage of testing its effectiveness on the process and results of student learning achievement.